The diagnostic boundary between autism spectrum disorder, intellectual developmental disorder and schizophrenia spectrum disorders. Issue 5 (7th September 2015) - Marco O. Bertelli, Dr; Bertelli, Marco O.; Piva Merli, Micaela; Bradley, Elspeth; Keller, Roberto; Varrucciu, Niccolò; Del Furia, Chiara; Panocchia, Nicola
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – During the last few years the prevalence of autism and Autism Spectrum Disorder (ASD) has increased greatly. A recurring issue is the overlap and boundaries between Intellectual Developmental Disorder (IDD), ASD and Schizophrenia Spectrum Disorders (SSD). In clinical practice with people with IDD, the alternative or adjunctive diagnosis of ASD or SSD is particularly challenging. The purpose of this paper is to define the boundaries and overlapping clinical characteristics of IDD, ASD and SSD; highlight the most relevant differences in clinical presentation; and provide a clinical framework within which to recognize the impact of IDD and ASD in the diagnosis of SSD. Design/methodology/approach – A systematic mapping of the international literature was conducted on the basis of the following questions: first, what are considered to be core and overlapping aspects of IDD, ASD and SSD; second, what are the main issues in clinical practice; and third, can key diagnostic flags be identified to assist in differentiating between the three diagnostic categories? Findings – Crucial clinical aspects for the differentiation resulted to be age of onset, interest towards others, main positive symptoms, and anatomical anomalies of the central nervous system. More robust diagnostic criteria and semeiological references are desirable. Originality/value – The present literature mapping provides a comprehensive description of the most relevant differences in the clinical presentation of ASD and SSD in persons with IDD.